HUBUNGAN ANTARA PERLAKUAN ORANGTUA DENGAN KEMANDIRIAN SISWA DALAM BELAJAR - Arora, Wisma; Erlamsyah, Erlamsyah; Syahniar, Syahniar (Universitas Negeri Padang, 2013)
The independence of learning is the process of moving the power of the individual who learns to move his or her potential in the study without any pressure or foreign influence from outside. External factors affecting the child's independence is a culture and parenting on children. In fact school students are passive in learning and students are not capable of doing their own tasks assigned by the teacher, because the parents do not give proper treatment to the children, especially in revision at home. This research aims to see how the relationship with self treatment of parents with student independenceÂ in learning in SMA N 1 Lembah Gumanti, Solok District. This research uses quantitative methods to the type of correlation. The research population was students of class XI and XII SMA N 1 Lembah Gumanti, Solok District.